2012
DOI: 10.1139/h11-125
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasma and erythrocyte phospholipid fatty acid profile in elite female water polo and football players

Abstract: The impact of chronic, intense exercise, such as in elite athletes, on phospholipids fatty acids (FA) composition has not been studied in women so far. This study aimed to investigate FA profiles in plasma and erythrocytes phospholipids in elite female water polo (N = 15) and football (N = 19) players in comparison with sedentary women. In spite of similar dietary patterns, as assessed by a food frequency questionnaire, plasma FA profile in the football players showed significantly higher proportions of steari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Their mean HS-Omega-3 Index was 4·97 ± 1·19% (Table 2), lower than in German patients with established coronary artery disease CAD (5·94 ± 1·41%, von Schacky, 2014). Using a different analytical method, a small study in female athletes found no significant difference in EPA or DHA, as compared with healthy controls (Arsić et al, 2012). Based on current literature, the athletes we studied might have an elevated risk for sudden cardiac death or for fatal and nonfatal myocardial infarction later in life.…”
Section: Hs-omega-3 Index 4·97 ± 1·19%mentioning
confidence: 87%
“…Their mean HS-Omega-3 Index was 4·97 ± 1·19% (Table 2), lower than in German patients with established coronary artery disease CAD (5·94 ± 1·41%, von Schacky, 2014). Using a different analytical method, a small study in female athletes found no significant difference in EPA or DHA, as compared with healthy controls (Arsić et al, 2012). Based on current literature, the athletes we studied might have an elevated risk for sudden cardiac death or for fatal and nonfatal myocardial infarction later in life.…”
Section: Hs-omega-3 Index 4·97 ± 1·19%mentioning
confidence: 87%
“…48,49 This is often found in elite athletes. [50][51][52] It was previously established that erythrocytes reflect the general FA metabolism in other organs and tissues. 53,54 A poor n-3 PUFAs status is often related to a low consumption of cold-water fish, as the primary source of EPA and DHA, and then to income status, national and social eating habits.…”
Section: Pufas Intake In Relation To Status Biomarkermentioning
confidence: 99%
“…On the other hand, in sports like water polo, there was a decrease of stearic acid (18:0) and an increase of palmitic (16:0) and palmitoleic (16:1) acids among the sportsmen in comparison with those in the control and the football players groups [21].…”
Section: Discussionmentioning
confidence: 85%
“…Arsic [21] made a comparative analysis of fatty acid profiles in erythrocyte membranes among female football and water polo players in both similar energetic exercise modalities (aerobic-anaerobic); they found a significantly higher proportion of oleic acid (18:1C) in the football group than in the control group. In anaerobic sports, such as boxing, predominant lower values of linoleic acid (18:2:6) were registered in comparison with those in the control group [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation